Fabrication of Li-Doped NiO Thin Films by Ultrasonic Spray Pyrolysis and Its Application in Light-Emitting Diodes - Víctor Hugo López-Lugo; Manuel García-Hipólito; Arturo Rodríguez-Gómez; Juan Carlos Alonso-Huitrón (Nanomaterials, 2023)
The fabrication of NiO films by different routes is important to extend and improve their applications as hole-transporting layers in organic and inorganic optoelectronic devices. Here, an automated ultrasonic pyrolysis spray method was used to fabricate NiO and Li-doped NiO thin films using nickel acetylacetonate and lithium acetate dihydrate as metal precursor and dimethylformamide as solvent. The effect of the amount of lithium in the precursor solution on the structural, morphological, optical, and electrical properties were studied. XRD results reveal that all the samples are polycrystalline with cubic structure and crystallite sizes in the range of 21 to 25 nm, without any clear trend with the Li doping level. AFM analysis shows that the crystallites form round-shaped aggregates and all the films have low roughness. The optical transmittance of the films reaches values of 60% to 77% with tendency upward as Li content is increased. The electrical study shows that the films are p-type, with the carrier concentration, resistivity, and carrier mobility depending on the lithium doping. NiO:Li (10%) films were successfully incorporated into inorganic light emitting diodes together with Mn-doped ZnS and ZnO:Al films, all deposited on ITO by the same ultrasonic spray pyrolysis technique.